Effect of air blast freezing and frozen storage on Escherichia coli survival, n-3 polyunsaturated fatty acid concentration and microstructure of Greenshell™ mussels. (September 2020) - Angane, Manasweeta; Gupta, Sravani; Fletcher, Graham C.; Summers, Graeme; Hedderley, Duncan I.; Quek, Siew Young
Abstract: This study highlighted the effect of air blast freezing and frozen storage on non-pathogenic Escherichia coli in Greenshell™ mussels ( Perna canaliculus ). Greenshell™ mussels were inoculated with a cocktail of 10 different strains of E. coli and their survival was monitored over a period of 84 days. Two freezing temperatures (−10 °C and −20 °C) and two inoculum concentrations, i.e. moderate (10 4 colony forming units/g (CFU/g) and high (10 7 CFU/g) were used. Enumeration of E. coli was carried out at regular intervals using the conventional 'most probable number' (MPN) and by SimPlate® methods. Results show that air blast freezing did not significantly reduce the non-pathogenic E. coli counts in the Greenshell™ mussels. However, subsequent frozen storage at −10 °C and −20 °C for a period of 84 days resulted in >1 log10 reduction in E. coli counts. Although, the use of different temperatures (−10 °C and −20 °C) did not show statistically significant ( p = 0.069) impact on E. coli counts, but based on the regression analysis, storage at −10 °C was slightly more effective at inactivating E. coli . Furthermore, compared to the conventional MPN method, the SimPlate® method was less sensitive and the correlation value between the two methods was found to be r 2 = 0.81 and r 2 = 0.75 for −10 °C and −20 °C, respectively. This research also investigated the effect of frozen storage on two components beneficial for health: eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and on microstructure changes during frozen storage. The total n-3 polyunsaturated fatty acid (PUFA) concentrations reduced significantly ( p < 0.05) after storing Greenshell™ mussels at −10 °C for a period of 84 days but the total n-3 PUFA levels did not reduce significantly ( p > 0.05) in mussels stored at −20 °C. In addition, the microstructure analysis revealed that frozen storage caused serious deformity in tissue structure of Greenshell™ mussels. Highlights: Average E. coli numbers reduced by 1.48 log10 units over 84 days frozen storage. F rozen storage is an effective method for reducing E. coli counts in mussels. Frozen storage caused serious deformity in microstructure of Greenshell™ mussels. EPA concentration did not reduce significantly ( p > 0.05) upon frozen storage. SimPlate® method was less sensitive than the conventional MPN method.